Palaeogeographical and archaeological records of natural changes of the Jordanowo-Niesulice subglacial channel near Lubrza, the Lubusz Lakeland - Ratajczak-Szczerba, Magdalena; Sobkowiak-Tabaka, Iwona; Okuniewska-Nowaczyk, Iwona (Wydział Nauk Geograficznych i Geologicznych Uniwersytetu im. Adama Mickiewicza, 2015)
The region of the Lubusz Lakeland in western Poland where there are a lot of subglacial channels provides opportunity for multi-proxy palaeoenvironmental reconstructions. None of them has not been the object of a specific study. The developmental history of the palaeolakes and their vicinity in the subglacial trough Jordanowo-Niesulice, spanning the Late Glacial and beginning of the Holocene, was investigated using geological research, lithological and geomorphological analysis, geochemical composition, palynological and archaeological research, OSL and AMS-radiocarbon dating. Geological research shows varied morphology of subglacial channel where at least two different reservoirs functioned in the end of the Last Glacial period and at the beginning of the Holocene. Mostly during the Bølling-Allerød interval and at the beginning of the Younger Dryas there took place melting of buried ice-blocks which preserved the analysied course of the Jordanowo-Niesulice trough. The level of water, and especially depth of reservoirs underwent also changes. Palynological analysis shows very diversified course of the Allerød interval.
Keywords: palaeogrography; palaeoclimate; subglacial channels/trough; pollen analysis; human impact/geoarchaeology